If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 129 = 2x + 5(2x + -8) Reorder the terms: 129 = 2x + 5(-8 + 2x) 129 = 2x + (-8 * 5 + 2x * 5) 129 = 2x + (-40 + 10x) Reorder the terms: 129 = -40 + 2x + 10x Combine like terms: 2x + 10x = 12x 129 = -40 + 12x Solving 129 = -40 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 129 + -12x = -40 + 12x + -12x Combine like terms: 12x + -12x = 0 129 + -12x = -40 + 0 129 + -12x = -40 Add '-129' to each side of the equation. 129 + -129 + -12x = -40 + -129 Combine like terms: 129 + -129 = 0 0 + -12x = -40 + -129 -12x = -40 + -129 Combine like terms: -40 + -129 = -169 -12x = -169 Divide each side by '-12'. x = 14.08333333 Simplifying x = 14.08333333
| x^2-x+7=6x-3 | | 10a+5(a-12)=0 | | E^2+16e+64y^2+15y=0 | | 61/30,400 | | 2x+(x+0.5)+x=7.5 | | 5s=7s+1 | | 3x+2y=19.50 | | -15x+3y=-45 | | -3(r-5)=-3(7r-5)+7r | | 9(8X-7)=32 | | 4+6(-6a+4)=-11+3a | | 2m+4+5=9 | | 10(42.85)-3=-6+3(42.85) | | -3(r-5)=(7r-5)+7r | | -8z+6(z+7)=1 | | 5x-7=6x-39 | | 3a+3(2a+8)=-(a-4) | | 2(3+2x)+x=2x+16 | | -5(7x+1)=-425 | | -3+3w+4= | | 5+3w-12=-7 | | -35x=-429 | | 5p-6(p-2)=-p | | 4x-3x+x-6+5x= | | 8n-(5n+7)=14 | | -25=5b | | Vf=Vi-(g)t | | 3+3(x-6)=3(2x+5) | | -(2y-1)=8(y+2)-7 | | 13/5-x/6=2x | | 0.3(0.1x+0.1)=-0.6 | | Y=-10+2 |